2018
DOI: 10.1021/jacs.7b13247
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nitride Nanothread Crystals Derived from Pyridine

Abstract: Carbon nanothreads are a new one-dimensional sp carbon nanomaterial. They assemble into hexagonal crystals in a room temperature, nontopochemical solid-state reaction induced by slow compression of benzene to 23 GPa. Here we show that pyridine also reacts under compression to form a well-ordered sp product: CNH carbon nitride nanothreads. Solid pyridine has a different crystal structure from solid benzene, so the nontopochemical formation of low-dimensional crystalline solids by slow compression of small aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(181 citation statements)
references
References 24 publications
(71 reference statements)
8
164
3
Order By: Relevance
“…The triangular lattice was constructed by first obtaining the equilibrium inter-tubular distance d 0 through a series of relaxation simulations under isothermal-isobaric ensemble 25 , that is, tuning the model with different initial distances in lateral and longitudinal directions and orientations. For nanothread-A, the inter-thread separation distance is~6.25 Å, which agrees well with previous simulation results and experimental measurements 20,48 . A larger d 0 of~7.25 Å was found for nanothread-C, which presumably is due to its helical morphology.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The triangular lattice was constructed by first obtaining the equilibrium inter-tubular distance d 0 through a series of relaxation simulations under isothermal-isobaric ensemble 25 , that is, tuning the model with different initial distances in lateral and longitudinal directions and orientations. For nanothread-A, the inter-thread separation distance is~6.25 Å, which agrees well with previous simulation results and experimental measurements 20,48 . A larger d 0 of~7.25 Å was found for nanothread-C, which presumably is due to its helical morphology.…”
Section: Methodssupporting
confidence: 91%
“…By turning the screw, the nanothread bundle will experience pure extension and thereby act as the mechanical energy storage system 1 . Considering the large variety of carbon nanothreads, nanothread derivatives (such as the carbon nitride nanothreads) 48 , and the huge variety of bundle configurations (with a mixture of threads of varying chirality), it is of great interest to carry out further experiments and theoretical works to explore the applications of carbon nanothread bundles for mechanical energy storage.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that benzene polymerizes into amorphous hydrogenated carbon under high pressure, and with anisotropic stress, a well‐ordered single‐crystal carbon nanothread was reported, which is recognized as an ultra‐thin sp 3 ‐carbon nanowire ,. Similarly, single‐crystal carbon nitride was synthesized by compressing pyridine slowly . Recently, it was reported that aniline forms diamond‐like polyaniline under external pressure and the hydrogen bond between the NH 2 groups is believed to be responsible for better crystallinity .…”
Section: Figurementioning
confidence: 99%
“…XRD data showed that the recovered samples contained a certain amount of crystalline components, but they did not identify specific substances [113]. Xiang Li et al recently obtained ordered sp 3 C 5 NH 5 carbon nitride nanothreads through the compression and decompression of pyridine [114]. The IR peak at 1117 cm −1 is identified as inter-ring C−N stretching, which suggests the polymerization of pyridine.…”
Section: Nitrilesmentioning
confidence: 99%